The role of Adaptor Protein 3 in cytotoxic T lymphocytes - Wenham, M (2009)
Cytotoxic T lymphocytes (CTL) kill virally infected and tumourigenic cells via the regulated secretion of specialised secretory lysosomes. These secretory lysosomes contain cytolytic effector molecules, such as perforin and granzymes, which are able to induce apoptosis in target cells. Secretion occurs at the contact point between the CTL and its target, in a highly structured region termed the immunological synapse (IS). Upon formation of the IS, CTL undergo polarisation of their microtubule cytoskeleton and movement of the microtubule organising centre (MTOC) to the IS. Secretory lysosomes are then able to polarise along microtubules, fuse with the plasma membrane and deliver their effector molecules to the IS. The Adaptor Protein 3 complex (AP-3) sorts transmembrane proteins to lysosomes and deficiency in AP-3 results in missorting of proteins from the lysosomal to plasma membrane. CTL from AP-3 deficient patients, who suffer from Hermansky-Pudlak Syndrome Type 2 (HPS2), show reduced killing of target cells. This thesis describes two new patients with HPS2, both with homozygous mutations in the AP3B1 gene, which codes for the β3A subunit of the AP-3 complex. CTL from the new HPS2 patients show reduced cytotoxicity, which is shown here to be due to impaired secretory lysosome polarisation towards the IS. This impairment is common to HPS2 CTL, but varies between patients. In order to determine differences between HPS2 and wild type CTL, the localisation of a range of lysosomal, cytolytic, transmembrane, inhibitory and activation marker proteins is examined. This shows that in HPS2 CTL, LAMP1, CD63 and CD9 are potential AP-3 cargos. In addition, a possible effect on the key lytic effector perforin is identified. Preliminary experiments to allow proteomic comparison of HPS2 and wild type CTL are also presented. Further investigation of these results will help to shed light on the mechanisms involved in secretory lysosome polarisation in CTL.